Mistaken Relationships in ‘Mistaken Identity’ by Nayantara Sahgal - Rao, G. Nageswara; Mohanacharyulu, Gomatam; Raghuram, M.V.; Kuma, K. Pavan (International Journal of Psychosocial Rehabilitation, 2020)
The results of technology have a great influence on the life of the individual and groups in the society. It results in various social groups in general and female gender groups in particular the ideas of liberation and freedom from the clutches of patriarchal society. A host of writers strongly pronounced the voices of women in the contemporary Indian writings in English in terms of their discrimination, identity and also proper status in the society. Some of the writers with their political ideologies and a few others individually proclaimed the struggle of women in the society for their rights. They championed the causes of women suppression and marched towards individual rebellion. The present paper exposes how the relationship between man and womandeteriorated in martial and extra marital relations in Nayantara Sahgal’s novel “Mistaken Identity” (1988). The revolutionary attitude of the characters and demands of the situations explain the relationship in married life and how those relations crossed the barriers of the socio-cultural borders. It also presents the arguments against the patriarchal impositions on the male-female relations which visage hugeencounters from the social life. She has taken hercharacters from different society as her protagonists. We can find that her novels revolve around female characters come from the different layers of the society, but facing similar problems from the society. All most all of her protagonists are emancipated, assertive, intellectual and independent women. Sahgal seems to be modern and liberal in approach and intends to establish new humanism and a new morality in the world. This paper presents the mistaken relationships of the characters in the novel Mistaken Identity to get identity and selfemancipation.